2019
DOI: 10.1093/rheumatology/kez173
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for acquisition and interpretation of MRI of the spine and sacroiliac joints in the diagnosis of axial spondyloarthritis in the UK

Abstract: Objectives To develop evidence-based recommendations on the use of MRI in the diagnosis of axial SpA (axSpA). Methods A working group comprising nine rheumatologists and nine musculoskeletal radiologists with an interest in axSpA was established, with support from the British Society of Spondyloarthritis (BRITSpA). Two meetings were held. In the first meeting, research questions were formulated. In the second meeting, the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 38 publications
1
33
0
Order By: Relevance
“…The novel findings of a distinct trend of decreasing inflammation and increasing fusion following TNFi treatment (1) are consistent with the proposed complementary role of mechanical stress and inflammation in the pathogenesis of axial SpA (4,5). New bone formation with ankylosis of the sacroiliac joints and the spine is the main type of structural damage to the skeleton that is observed in SpA (4) and used in the diagnosis of ankylosing spondylitis (AS) (6,7).…”
Section: Do Microinjury Mechanisms Complement Inflammation In Sacroilsupporting
confidence: 52%
See 2 more Smart Citations
“…The novel findings of a distinct trend of decreasing inflammation and increasing fusion following TNFi treatment (1) are consistent with the proposed complementary role of mechanical stress and inflammation in the pathogenesis of axial SpA (4,5). New bone formation with ankylosis of the sacroiliac joints and the spine is the main type of structural damage to the skeleton that is observed in SpA (4) and used in the diagnosis of ankylosing spondylitis (AS) (6,7).…”
Section: Do Microinjury Mechanisms Complement Inflammation In Sacroilsupporting
confidence: 52%
“…New bone formation with ankylosis of the sacroiliac joints and the spine is the main type of structural damage to the skeleton that is observed in SpA (4) and used in the diagnosis of ankylosing spondylitis (AS) (6,7). A priority research agenda for interpreting MRI of the spine and sacroiliac joints in the diagnosis of axial SpA is to differentiate which structural MRI lesions may be stress-or biomechanically induced, as opposed to other active or inflammation-related lesions (5).…”
Section: Do Microinjury Mechanisms Complement Inflammation In Sacroilmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that PDFF 90 enabled separation of patients with and without fat metaplasia. Fat metaplasia can contribute to diagnosis [6,7] and is also a prognostic factor, since patients with fat metaplasia are more likely to fuse their sacroiliac joints [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of SpA is often difficult due to the complex nature of pain in young patients [2], and delays in diagnosis and treatment are common [3]. Identification of bone marrow oedema on MRI is of importance for showing inflammation of the sacroiliac joints and supports diagnosis of axial SpA [4][5][6][7]. This directly influences the decision to treat patients with diseasemodifying or biologic drugs [5].…”
Section: Introductionmentioning
confidence: 99%